SOCIAL LEARNING THEORY IN CUSTOMER ENGAGEMENT TO INCREASE IMPULSIVE BUYING BEHAVIOR - Wahyuni, Annisa Citra; Masnita, Yolanda; Kurniawati, Kurniawati (Universitas Nusa Cendana, 2025)
This research aims to investigate the influence of social learning theory on customer engagement and its role in promoting impulsive buying behavior within the context of live-streaming commerce. Utilizing a quantitative approach, the study employed Structural Equation Modeling (SEM) analysis through AMOS software to evaluate the effects of various influencer characteristics on consumer behavior. The findings reveal that factors such as influencer attractiveness, trustworthiness, and interactivity significantly enhance customer engagement and, consequently, encourage impulsive buying tendencies among viewers. This study provides valuable insights for businesses leveraging influencer marketing strategies, highlighting the importance of creating compelling and trustworthy interactions that can stimulate consumer purchasing decisions. Keywords: Social Learning Theory; Live-streaming Commerce; Influencer Marketing; Customer Interaction; Impulsive Purchasing Behavior